Analysis of Nutritional Composition in 23 Kinds of Edible Fungi - Qiannan Yu; Meijuan Guo; Bin Zhang; Hao Wu; Yan Zhang; Lantian Zhang (Journal of Food Quality)
To explore the differences in the main nutritional composition of 23 kinds of common edible fungi in the market, the moisture, ash, protein, fat, dietary fiber, carbohydrates, polysaccharides, and energy were analyzed using national standard methods. The results showed that the 23 kinds of edible fungi varied greatly in nutritional composition. Based on dry weight, the moisture content was 6.9∼15.5 g/100 g, the ash content ranged from 1.3 to 10.1 g/100 g, the protein content ranged from 8.5 to 36.9 g/100 g, the fat content was 0.5∼3.9 g/100 g, the dietary fiber content was between 14.4∼70.2 g/100 g, the carbohydrate content is 0.5∼37.3 g/100 g, the polysaccharide content was 2.1∼8.3 g/100 g, and the energy is about 751∼1322 100 g/kJ. All the 23 kinds of edible fungi can be regarded as high-protein low-fat foods, which have their own advantages in terms of nutritional value. This study provides reference for people to use edible fungi in a more scientific and reasonable way.